Pembelajaran melalui Brain Based Learning dalam Pendidikan Anak Usia Dini - Nikmah, Alfu (PIAUD Universitas Islam Negeri Sunan Kudus, 2015)
There are many innovations that have been made in education, both relating to curriculum, teaching materials, instructional media, learning model and others. Brain based learning or brain-based learning as a learning model actually has its own interesting bargaining power to be applied in the learning process ecpecially in the Early Childhood Education. Brain-based teaching and learning offers a concept to create learning oriented to the empowerment of student’s brain potential. There are three strategies that can be developed in implementation of brain based learning. First, create a learning environment that challenges students’ thinking ability. Second, creating a fun learning environment, third, create a situation of active and meaningful for students (active learning). By knowing the brain development in children, parents and teachers can apply the appropriate education and teaching to the children.